2021
DOI: 10.1186/s13717-021-00311-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender plasticity uncovers multiple sexual morphs in natural populations of Cedrus deodara (Roxb.) G. Don

Abstract: Background The expression of gender in gymnosperms is challenging because the extent of variability in gender segregations in tree crowns and selection pressure of nature can modify the gender through time. Methods An in-depth investigation on spatial segregation of genders in tree crowns and sex expression of a total of 500 trees in five different natural populations of Cedrus deodara was carried out and verified the occurrence of subdioecious (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…On the contrary, the height and diameter of Pinus roxurghii have a negative significant correlation with pollen grains per tree (Khanduri and Sharma, 2002a), and the height of the tree in Populus and Acer negundo have a negative significant correlation with pollen grains per tree (Molina et al, 1996). The non-significant effect of tree sizes on male cone production and the significant effect on female cone production was reported in Cedrus deodara (Khanduri et al, 2021). In a detailed study of six oaks species, negative correlations were found between pollen grains per anther, the number of anthers per flower, and the number of flowers per catkin.…”
Section: Pollen Productionmentioning
confidence: 89%
“…On the contrary, the height and diameter of Pinus roxurghii have a negative significant correlation with pollen grains per tree (Khanduri and Sharma, 2002a), and the height of the tree in Populus and Acer negundo have a negative significant correlation with pollen grains per tree (Molina et al, 1996). The non-significant effect of tree sizes on male cone production and the significant effect on female cone production was reported in Cedrus deodara (Khanduri et al, 2021). In a detailed study of six oaks species, negative correlations were found between pollen grains per anther, the number of anthers per flower, and the number of flowers per catkin.…”
Section: Pollen Productionmentioning
confidence: 89%
“…The study of reproduction in C. deodara species has revealed a large variability in pollen and ovule characters (Johri and Vasil 1961;Chowdhury 1961;Konar and Oberoi 1969;Owens 1995a, 1995b;Sharma 2002, 2009), as well as in the sexual expression of the tree depending on year, site, and tree size (Khanduri and Sharma, 2010;Sharma and Bhondge 2016;Khanduri et al 2021). Some limited studies have reported significant variability in pollen size of C. atlantica depending on several parameters, including site conditions, genome size, adaptations required for wind pollination, and irregular pollen development (Smith 1923;Derridj et al 1991;Bell et al 2017;Bell et al 2018aBell et al , 2018b.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations have shown several factors alter sex expression in monoecious plants, including sex allocation (Pannell, 2017), environmental pressure, and adaptation to wind pollination (Walas et al, 2018). The tree size also significantly impacts sex expression, with females and monoecious trees often found in higher-diameter classes, which can compensate for a more reproductive investment (Khanduri et al, 2021).…”
Section: Introductionmentioning
confidence: 99%